Current status of pulmonary artery denervation - Davies, Mark G.; Miserlis, Dimitrios; Hart, Joseph P. (Frontiers in Cardiovascular Medicine, 2022)
Pulmonary hypertension is a progressive disease with a poor long-term prognosis and high mortality. Pulmonary artery denervation (PADN) is emerging as a potential novel therapy for this condition. The basis of pursuing a sympathetic denervation strategy has its origins in a body of experimental translation work that has demonstrated that denervation can reduce sympathetic nerve activity in various animal models. This reduction in pulmonary sympathetic nerve activity is associated with a reduction in pathological pulmonary hemodynamics in response to mechanical, pharmacological, and toxicologically induced pulmonary hypertension. The most common method of PADN is catheter-directed thermal ablation. Since 2014, there have been 12 reports on the role of PADN in 490 humans with pulmonary hypertension (311:179; treated: control). Of these, six are case series, three are randomized trials, and three are case reports. Ten studies used percutaneous PADN techniques, and two combined PADN with mitral and/or left atrial surgery. PADN treatment has low mortality and morbidity and is associated with an improved 6-minute walking distance, a reduction in both mean pulmonary artery pressure and pulmonary vascular resistance, and an improvement in cardiac output. These improved outcomes were seen over a median follow-up of 12 months (range 2–46 months). A recent meta-analysis of human trials also supports the effectiveness of PADN in carefully selected patients. Based on the current literature, PADN can be effective in select patients with pulmonary hypertension. Additional randomized clinical trials against best medical therapy are required.